2022
DOI: 10.1002/tcr.202200118
|View full text |Cite
|
Sign up to set email alerts
|

A Review of MnO2 Composites Incorporated with Conductive Materials for Energy Storage

Abstract: Manganese dioxide (MnO2) has been widely used in the field of energy storage due to its high specific capacitance, low cost, natural abundance, and being environmentally friendly. However, suffering from poor electrical conductivity and high dissolvability, the performance of MnO2 can no longer meet the needs of rapidly growing technological development, especially for the application as electrode material in metal‐ion batteries and supercapacitors. In this review, recent studies on the development of binary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 190 publications
0
7
0
Order By: Relevance
“…The insufficient supercapacitor electrode performance of plain metal oxides was stated in [ 7 , 213 ]; it has been attributed to the frequently poor electronic conductance and solubility of the compounds, at least in certain redox states of the active metal ions resulting in fast capacity fading. As a remedy, nanostructuring has been proposed and examined [ 63 , 202 , 214 , 215 , 216 , 217 ]; the preparation of composites, including those with ICPs, has been recommended elsewhere [ 5 , 7 , 71 , 213 , 214 , 218 , 219 , 220 ]. To call such composite-formation a modification may be misleading [ 5 ].…”
Section: The Combinationsmentioning
confidence: 99%
“…The insufficient supercapacitor electrode performance of plain metal oxides was stated in [ 7 , 213 ]; it has been attributed to the frequently poor electronic conductance and solubility of the compounds, at least in certain redox states of the active metal ions resulting in fast capacity fading. As a remedy, nanostructuring has been proposed and examined [ 63 , 202 , 214 , 215 , 216 , 217 ]; the preparation of composites, including those with ICPs, has been recommended elsewhere [ 5 , 7 , 71 , 213 , 214 , 218 , 219 , 220 ]. To call such composite-formation a modification may be misleading [ 5 ].…”
Section: The Combinationsmentioning
confidence: 99%
“…In this regard, MnO 2 has been widely used in VOC clearance for its unique properties, such as multiple valence of manganese (Mn 2+ , Mn 3+ , and Mn 4+ ), 6,7 strong oxidizability, low cost, and high environmental compatibility. 8 In addition, Mn oxide is a typical metal oxide that contains numerous electron centers, which could adsorb O 2 forming electron-rich species, and gives abundant lattice oxygen to promote the catalytic reaction. 9 Various morphologies of MnO 2 , such as 0D tunnel structure nanoparticles, 10 1D tunnel structure nanowires, nanorods, nanotubes, nanobelts, 11,12 2D layer structure, 13 and 3D mesh structure, 14,15 have been synthesized and used to degrade VOCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these methods, the hydrothermal method has been widely applied owing to its no-template and mild hydrothermal conditions in the synthesis process. 8,20 In addition, Ye et al found that MnO 2 -CeO 2 synthesized using the hydrothermal method had higher Hg 0 removal efficiency at lower temperatures. 21 The work reported by Yao et al showed that the MnO x -CeO 2 catalyst synthesized using the hydrothermal method achieved the excellent catalytic performance for NO at low temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations